Hak-Hak Pekerja Kontrak dalam Perspektif Hukum Ketenagakerjaan di Tinjau dalam UU No. 13 Tahun 2003 (International Forum of Researchers and Lecturers, 2024)
Contract workers are workers who are contracted within a certain time, it could be two years, three years or more. In general, workers have a work contract with the company where they work, there are many workers in Indonesia who experience violations of legal protection of labor rights and obligations, and what are the rights and obligations of labor which is the basis of this research. The purpose to be achieved in this paper is to find out what are the rights of labor contracts to workers who often have no knowledge of what is about labor contracts. This article discusses the rights of contract workers based on Indonesian labor law regulations. Contract workers, who are employed under a fixed-term employment agreement (PKWT), have rights that are guaranteed by law although they differ from those of permanent workers. Some of these rights include wages, social security, employment protection, and the right to compensation in the event of termination before the contract ends.